Safety and efficacy at 240 weeks of different raltegravir formulations in children with HIV-1: a phase 1/2 open label, non-randomised, multicentre trial. Issue 12 (December 2018) - Nachman, Sharon; Alvero, Carmelita; Teppler, Hedy; Homony, Brenda; Rodgers, Anthony J; Graham, Bobbie L; Fenton, Terence; Frenkel, Lisa M; Browning, Renee S; Hazra, Rohan; Wiznia, Andrew A
Summary: Background: Raltegravir is an integrase inhibitor approved for use in adults and children with HIV-1 infection, but there are no data on the long-term use of this medication in children. We aimed to assess the long-term safety, tolerability, pharmacokinetics, and efficacy of multiple raltegravir formulations in children aged 4 weeks to 18 years with HIV-1 infection. Methods: In this phase 1/2 open-label multicentre trial (IMPAACT P1066), done in 43 IMPAACT network sites in the USA, South Africa, Brazil, Botswana, and Argentina, eligible participants were children aged 4 weeks to 18 years with HIV-1 infection who had previously received antiretroviral therapy (ART), had HIV-1 RNA higher than 1000 copies per mL, and no exposure to integrase inhibitors. Participants were separated into five age groups and enrolled in six cohorts. Three formulations of open-label raltegravir—adult tablets, chewable tablets, and granules for oral suspension—were added to individualised optimised background therapy, according to the age and weight of participants. The primary outcome at 48 weeks has been previously reported. In the 240-week follow-up, outcomes of interest included graded clinical and laboratory safety of raltegravir formulations during the study and virological efficacy (with virological success defined as HIV-1 RNA reduction of >1 log10 from baseline or HIV-1 RNA <400 copies per mL) at week 240. The primary analysis group for safety and efficacy comprised patients treated only with the final selected dose of raltegravir. This trial is registered withClinicalTrials.gov, numberNCT00485264 . Findings: Between August, 2007, and December, 2012, 220 patients were assessed for eligibility, and 153 were enrolled and treated. Of these patients, 122 received only the final selected dose of raltegravir (63 received adult tablets, 33 chewable tablets, and 26 oral granules), and one was not treated. There were few serious clinical or laboratory safety events noted, with two patients having a drug-related adverse event (skin rash), which led one patient to discontinue the study treatment. The addition of raltegravir to an individually optimised ART regimen resulted in virological success at week 240 in 19 (44·2%, 95% CI 29·1–60·1) of 43 patients receiving 400 mg tablets, 24 (77·4%, 58·9–90·4) of 31 patients receiving the chewable tablets, and 13 (86·7%, 59·5–98·3) of 15 patients receiving oral granules. Among patients with virological failure, raltegravir resistance was noted in 19 (38%) of 50 patients who had virological rebound after initial suppression and had samples at virological failure available for testing. Interpretation: Our study suggests that raltegravir can be used for the treatment of HIV-1 infection in children as young as 4 weeks, with the expectation of long-term safety and efficacy, but should be used with caution among older children who had previous extensive antiretroviral therapy. Funding: National Institute of Allergy and Infectious Diseases, National Institute of Child Health and Human Development, National Institute of Mental Health, and Merck.